Adsorption, thermodynamic, and electrochemical studies of ketosulfide for mild steel in acidic medium - Hebbar, N. (Taylor & Francis, 2015)
The corrosion inhibition efficiency of ketosulfide was investigated by electrochemical methods in 1 M HCl solution at 303-333K. The polarization method showed mixed-type inhibition characteristics of ketosulfide. Adsorption behavior of ketosulfide was studied and which followed the Langmuir adsorption isotherm. Thermodynamic parameters were also calculated using Gibb's Helmholtz, Van't Hoff and basic themodynamic equations. Activation parameters were calculated using Arrhenius and transition state equations. The morphology of mild steel surface was examined by scanning electron microscopic images in the absence and presence of ketosulfide.